Cost behaviour and reporting frequency during the COVID-19 outbreak - Finne, Gustav; Haga, Jesper; Sundvik, Dennis (2024)
Funding Information: We appreciate helpful comments from Per Olsson (the associate editor), two anonymous reviewers, Mansoor Afzali, Patricia Bromley, Ellie Chapple, Sander De Groote, Peter Frii, Henrik Höglund, Henry Jarva, Bjørn Jørgensen, Juha-Pekka Kallunki, Jukka Kettunen, Eva Labro, Zeping Pan, Zihang Peng, Carsten Rohde, Petri Sahlström, Amir Sasson, David Schröder, Stefan Sundgren, Stephen Taylor, Aljoša Valentinčič, Sami Vähämaa and participants in the 2021 Nordic Accounting Conference, XVI International Accounting Research Symposium and workshop participants at Copenhagen Business School, Stanford University, Queensland University of Technology, Umeå University, University of Oulu, University of Vaasa, University of Technology Sydney, UNSW Sydney, and Victoria University of Wellington. We gratefully acknowledge financial support from the Foundation for Economic Education, Hanken Support Foundation, OP Group Research Foundation, the Finnish Foundation for Share Promotion, the Foundation for the Advancement of Finnish Securities Markets, and research assistance from Jiangnan Zhang. Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. We examine the effect of financial reporting frequency on cost management decisions in crisis situations, with a focus on the COVID-19 outbreak. Using the European setting, we find that quarterly reporters exhibit greater cost elasticity relative to semi-annual reporters, meaning they had larger changes in cost for each change in sales. When allowing for cost asymmetry, we see that our results are driven by firms with decreases in sales and that quarterly reporters reduced their costs more. Additional analyses show that managerial learning and monitoring pressure might be potential channels behind the results and that there is a positive performance effect in the short run. Peer reviewed